The RNA N6-Methyladenosine Methyltransferase METTL3 Promotes the Progression of Kidney Cancer via N6-Methyladenosine-Dependent Translational Enhancement of ABCD1 - Shi, Yue; Dou, Yanliang; Zhang, Jianye; Qi, Jie; Xin, Zijuan; Zhang, Mingxin; Xiao, Yu; Ci, Weimin (Frontiers in Cell and Developmental Biology, 2021)
The role of N6-methyladenosine (m6A)-modifying proteins in cancer progression depends on the cell type and mRNA affected. However, the biological role and underlying mechanism of m6A in kidney cancer is limited. Here, we discovered the variability in m6A methyltransferase METTL3 expression was significantly increased in clear cell renal cell carcinoma (ccRCC) the most common subtype of renal cell carcinoma (RCC), and high METTL3 expression predicts poor prognosis in ccRCC patients using a dataset from The Cancer Genome Atlas (TCGA). Importantly, knockdown of METTL3 in ccRCC cell line impaired both cell migration capacity and tumor spheroid formation in soft fibrin gel, a mechanical method for selecting stem-cell-like tumorigenic cells. Consistently, overexpression of METTL3 but not methyltransferase activity mutant METTL3 can promote cell migration, spheroid formation in cell line and tumor growth in xenograft model. Transcriptional profiling of m6A in ccRCC tissues identified the aberrant m6A transcripts were enriched in cancer-related pathways. Further m6A-sequencing of METTL3 knockdown cells and functional studies confirmed that translation of ABCD1, an ATP-binding cassette (ABC) transporter of fatty acids, was inhibited by METTL3 in m6A-dependent manner. Moreover, knockdown of ABCD1 in ccRCC cells decreased cancer cell migration and spheroid formation, and upregulation of ABCD1 acts as an adverse prognosis factor of kidney cancer patients. In summary, our study identifies that METTL3 promotes ccRCC progression through m6A modification-mediated translation of ABCD1, providing an epitranscriptional insight into the molecular mechanism in kidney cancer.